Kampanye KOMNAS Perempuan Pada Kampanye 16 Hari Anti Kekerasan Terhadap Perempuan - Casa Bilqis Savitri; Wina Puspita Sari (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2019)
The 16 Days Against Women Violence Campaign is a campaign to encourage liberation struggles against women throughout the world. As a national human right in Indonesia. This campaign has been carried out since 2003 and is routinely carried out every period with a 16-day campaign set in November. Problems in the 16-Day Campaign Against Violence Against Women, this campaign has been running for 15 years, but this is not directly proportional to the protected numbers against women has increased over the past three years. The main theory in this research is campaign theory using Nowak & Warneryd's campaign model. The method used is a descriptive qualitative research method that looks for facts with the right interpretation. Descriptive research on problems in society, views, and processes - ongoing parts and effects of phenomena. Komnas Perempuan is still too broad in setting its campaign targets, as well as a lot of messages to be conveyed. the extent of challenging the campaign audience makes KOMNAS Perempuan against barriers ranging from language and culture, there is a GAP about knowledge of challenges, to obstacles in choosing what campaign techniques to use. In the 16 Days Anti Violence against Women campaign, KOMNAS Perempuan chose to generalize the message to be conveyed, accepting their own challenges, which made the objectives of the 16 Days Anti Violence Against Women Campaign unsuccessful. Keywords: Campaign, KOMNAS Perempuan, Violence